Digital Transformations in the Bank Sector - ARTEMIEVAІ.; ZALІUBOVSKAS. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2023)
The article contains an analysis of the transformation in the operation of commercial banks in the context of digitalization. The following characteristics of bank products are defined and described as a promising area of the transformations in the digital banking: convenience of use; openness and transparence; visual attractiveness and functional design; user-friendly character of services; high reliability; safety and confidentiality; high speed. It is shown that for practical implementation of the abovementioned characteristics inside the banks the favorable climate for the work with digital innovations needs to be created. The factors of success, to the author’s opinion, should include the existence of clear goals and effective strategies for their achievement, signing of partner agreements, extension and deepening of digital competencies (using technologies of big data, artificial intellect, machine learning, cloud computations, blockchain, etc.), introduction of omnichannel interactions with clients, well-established corporative culture of the bank. Internal and external problems faced by banks in implementing digital transformation are revealed. The most appropriate areas of digital transformations for various types of banks are outlined. It is substantiated that big banks should use their resources and competencies in carrying out large-scale digital transformations, whereas small and medium banks need to find their product niches for business expansion. The conclusion is made that at the current phase of the bank sector evolution digital competencies have become a principal driving force of the competition on the financial intermediation market. Using of intellectual technological decisions as a critical factor of success can help banks accelerate digital transformations and enhance their effectiveness.